Human articular chondrocytes secrete parathyroid hormone-related protein and inhibit hypertrophy of mesenchymal stem cells in coculture during chondrogenesis - Fischer, Jennifer; Dickhut, Andrea; Rickert, Markus; Richter, Wiltrud (Arthritis & rheumatism, 2010)
Objective The use of bone marrow-derived mesenchymal stem cells (MSCs) has shown promise in cell-based cartilage regeneration. A yet-unsolved problem, however, is the unwanted up-regulation of markers of hypertrophy, such as alkaline phosphatase (AP) and type X collagen, during in vitro chondrogenesis and the formation of unstable calcifying cartilage at heterotopic sites. In contrast, articular chondrocytes produce stable, nonmineralizing cartilage. The aim of this study was to address whether coculture of MSCs with human articular chondrocytes (HACs) can suppress the undesired hypertrophy in differentiating MSCs. Methods MSCs were differentiated in chondrogenic medium that had or had not been conditioned by parallel culture with HAC pellets, or MSCs were mixed in the same pellet with the HACs (1:1 or 1:2 ratio) and cultured for 6 weeks. Following in vitro differentiation, the pellets were transplanted into SCID mice. Results The gene expression ratio of COL10A1 to COL2A1 and of Indian hedgehog (IHH) to COL2A1 was significantly reduced by differentiation in HAC-conditioned medium, and less type X collagen protein was deposited relative to type II collagen. AP activity was significantly lower (P < 0.05) in the cells that had been differentiated in conditioned medium, and transplants showed significantly reduced calcification in vivo. In mixed HAC/MSC pellets, suppression of AP was dose-dependent, and in vivo calcification was fully inhibited. Chondrocytes secreted parathyroid hormone-related protein (PTHrP) throughout the culture period, whereas PTHrP was down-regulated in favor of IHH up-regulation in control MSCs after 2-3 weeks of chondrogenesis. The main inhibitory effects seen with HAC-conditioned medium were reproducible by PTHrP supplementation of unconditioned medium. Conclusion HAC-derived soluble factors and direct coculture are potent means of improving chondrogenesis and suppressing the hypertrophic development of MSCs. PTHrP is an important candidate soluble factor involved in this effect.